Morphological and functional differences in the elbow extensor muscle between highly trained male and female athletes - Ichinose, Y.; Kanehisa, H.; Ito, M.; Kawakami, Y.; Fukunga, T. (European Journal of Applied Physiology, 1998)
The purpose of this study was to investigate the difference in the morphological and functional aspects of the triceps brachii muscle between highly trained male and female athletes who were members of the 1996 Japanese Olympic teams in each of three different events: soccer, gymnastics and judo.